Subsidy Reforms in the Middle East and North Africa Region : A Review - Verme, Paolo (World Bank, Washington, DC, 2016)
The paper takes stock of eight country studies and a cross-country analysis to review the experience with subsidy reforms in the Middle East and North Africa region between 2010 and 2014. This unprecedented period of subsidy reforms occurred during a period of extraordinary political changes, which makes this particular experience unique. The paper reviews the facts and the different paths to reforms taken by different countries faced with different challenges, and discusses the pros and cons of alternative policy options. It concludes with an assessment of the experiences and a discussion on future prospects.